2009
DOI: 10.1029/2008jd011300
|View full text |Cite
|
Sign up to set email alerts
|

Particulate emissions from commercial shipping: Chemical, physical, and optical properties

Abstract: , 39% OM, and 15% BC and differs from inventories that used 81%, 14%, and 5% and 31%, 63%, and 6% SO 4 2À , OM, and BC, respectively. SO 4 2À and OM mass were found to be dependent on fuel sulfur content as were SSA, hygroscopicity, and CCN concentrations. BC mass was dependent on engine type and combustion efficiency. A plume evolution study conducted on one vessel showed conservation of particle light absorption, decrease in CN > 5 nm, increase in particle hygroscopicity, and an increase in average particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
242
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(266 citation statements)
references
References 68 publications
19
242
4
1
Order By: Relevance
“…Partially this can be caused by the fact that also SO 3 and sulphuric acid are formed by the combustion of sulphur containing fuels. During emission studies this has been found to account for between 1 and 8 % of the total sulphur content (Moldanová et al, 2009;Agrawal et al, 2008;Lack et al, 2009;Alföldy et al, 2013). During the SIRENAS-R campaign 7 % of the measured sulphur was present as particle sulphate (Alföldy et al, 2013) and consequently it cannot fully explain the observed difference.…”
Section: Stena Hollandicamentioning
confidence: 99%
See 1 more Smart Citation
“…Partially this can be caused by the fact that also SO 3 and sulphuric acid are formed by the combustion of sulphur containing fuels. During emission studies this has been found to account for between 1 and 8 % of the total sulphur content (Moldanová et al, 2009;Agrawal et al, 2008;Lack et al, 2009;Alföldy et al, 2013). During the SIRENAS-R campaign 7 % of the measured sulphur was present as particle sulphate (Alföldy et al, 2013) and consequently it cannot fully explain the observed difference.…”
Section: Stena Hollandicamentioning
confidence: 99%
“…If each of the two setups is seen as an instrument to measure FSC, the uncertainty between the two instruments can be estimated as (Beijk et al, 2008;Kendall and Stuart, 1969) …”
Section: Sniffing Instrumentsmentioning
confidence: 99%
“…The composition of particles from ship exhausts is dominated by organic carbon (OC), ash, soot, and sulfate, of which sulfate and OC increase upon cooling. 19 Lack et al 25 show with extensive field data from measurements in ship plumes of some 200 ships how the particulate emissions of sulfate and organic matter increase with the fuel sulfur content, whereas black carbon (BC) appears to have an inverse correlation with sulfur content. The correlation between BC emissions and the fuel sulfur content is described as secondary to engine type.…”
Section: Studymentioning
confidence: 99%
“…Consequently, nearly all solid fuels in South Asia, Africa, and Latin America are allocated to cooking stoves. For Asia, we draw on the past and ongoing collaboration on the development of the GAINS-Asia model (Amann et al, 2008;Klimont et al, 2009;Zhang et al, 2006;Zhao et al, 2013), where assumptions on the split between heating and cooking, as well as fuel used in medium-sized boilers, were made, together with several peer-reviewed publications (e.g. Aggarwal and Chandel, 2004;Venkataraman et al, 2010).…”
Section: Residential Combustion: Cooking Heating Lightingmentioning
confidence: 99%